Ketogenic diets are associated with an elevated risk of hypertension: Insights from a cross-sectional analysis of the NHANES 2007–2018 - Xiaolong Qu; Yuping Liu; Lei Huang; Fang Wan (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Background: The ketogenic diet (KD) is widely used for weight loss in obese individuals; however, its potential impact on hypertension risk remains uncertain. Methods: We used cross-sectional data from the 2007–2018 to National Health and Nutrition Examination Survey (NHANES) to investigate the association between the dietary ketogenic ratio (DKR) and hypertension prevalence. Dietary intake information was obtained through a comprehensive 24-h dietary recall interview. The DKR values were computed using a specialized formula. Multiple logistic regression analysis was employed to examine this association, whereas nonlinear relationships were assessed using restricted cubic splines. Inflection points were determined using two-piecewise linear regression analysis. Subgroup analyses based on age were also performed. Results: In a fully adjusted multivariate logistic regression model accounting for confounding variables, DKR was significantly associated with hypertension (OR, 1.24; 95 % CI: 1.00–1.53; P = 0.045). Moreover, individuals in the highest quartile of DKR exhibited a significantly elevated risk of hypertension compared with those in the lowest quartile (OR, 1.15; 95 % CI: 1.07–1.24; P < 0.001). Additionally, restricted cubic spline analysis revealed a linear relationship between DKR and the risk of hypertension, with a turning point identified at 3.4 units on the measurement scale employed for this study's purposes. Subgroup analyses indicated that this association between DKR and hypertension was particularly pronounced among individuals aged ≥40 years, especially those age group–40-60. We further observed that a multivariate linear regression analysis revealed a significant positive correlation between DKR and DBP in a fully adjusted model (β, 0.42; 95 % CI: 0.12–0.87; P = 0.018), indicating that as DKR increased, there was an accompanying increase in DBP. However, no significant correlation was found between SBP and DKR (β, 0.11; 95 % CI: −0.37-0.59; P = 0.655). Conclusion: The KD may enhance susceptibility to hypertension in middle-aged and elderly populations in the United States, exhibiting a strong association with elevated diastolic blood pressure, while no significant correlation was observed with increased systolic blood pressure.